Motivasi Minat Belajar Putra Putri Warga Kelurahan Jagakarsa - Sri Widyastuti; Bayu Retno; Irma Permata (SULUH: Jurnal Abdimas, 2019)
Motivation is important in shaping how much students ask to learn. Motivation also affects how many students will learn from a learning activity, or how much absorption of students in capturing the information presented to students. Improving student learning motivation is one of the integral activities that must exist in learning activities. In addition to providing and transferring knowledge, the teacher also has the duty to increase children's motivation in learning. We cannot deny that students' motivation to learn from one another is very different, for this reason it is important for the teacher to always provide motivation to students so that students always have the spirit of learning and be able to become students who excel and can develop themselves optimally.